Stuttering adaptation, reactive inhibition and spontaneous recovery - MN, Hegde (Journal of All India Institute of Speech and Hearing, 1971)
It was observed during the shadowing therapy sessions to the stutterers that in any single session of thirty minutes duration the number of stuttered words went on decreasing but only to a certain point. There after the number of stuttered words gradually started increasing, finally reaching the initial level. Thus the problem of the present investigation was to determine whether this tendency for initial drop and a gradual increase in the number of stuttered words was something particular to speech-shadowing or is also true of ordinary continuous reading.